2013
DOI: 10.1111/epi.12341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical dissection of early onset absence epilepsy in children and prognostic implications

Abstract: SUMMARYPurpose: To investigate whether patients with typical absence seizures (TAS) starting in the first 3 years of life, conformed to Panayiotopoulos's definition of childhood absence epilepsy (CAE), show different electroclinical course than those not fulfilling CAE criteria. Methods: In this multicenter retrospective study, we choose a fixed duration follow-up of 36 months to examine the electroclinical course of epilepsy in all children with TAS starting before 3 years of age. The probands who fulfilled P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The GGE diagnoses included mainly the classical four phenotypes of childhood or juvenile absence epilepsy (CAE, JAE), juvenile myoclonic epilepsy (JME), or GGE with generalized tonic-clonic seizures alone (EGTC); we included few cases with early-onset absence epilepsy (EOAE, defined as beginning below three years of age), epilepsy with myoclonic absences (EMA) and up to 30% unclassified GGE, since these entities in our view are close to classical GGE. For EOAE it has been recently suggested by a large study that it is likely genetically similar to classical CAE 11 , EMA may also have genetic overlaps with GGE 12 and we often find in family studies both well classified and unclassified GGE cases in the same pedigrees (see appendix for detailed phenotypes in all cohorts). The first, discovery WES case cohort included 152 subjects (after quality control (QC)) with GGE from multiplex families, collected by the Epicure and the EuroEPINOMICS-CoGIE consortia.…”
Section: Participantssupporting
confidence: 50%
“…The GGE diagnoses included mainly the classical four phenotypes of childhood or juvenile absence epilepsy (CAE, JAE), juvenile myoclonic epilepsy (JME), or GGE with generalized tonic-clonic seizures alone (EGTC); we included few cases with early-onset absence epilepsy (EOAE, defined as beginning below three years of age), epilepsy with myoclonic absences (EMA) and up to 30% unclassified GGE, since these entities in our view are close to classical GGE. For EOAE it has been recently suggested by a large study that it is likely genetically similar to classical CAE 11 , EMA may also have genetic overlaps with GGE 12 and we often find in family studies both well classified and unclassified GGE cases in the same pedigrees (see appendix for detailed phenotypes in all cohorts). The first, discovery WES case cohort included 152 subjects (after quality control (QC)) with GGE from multiplex families, collected by the Epicure and the EuroEPINOMICS-CoGIE consortia.…”
Section: Participantssupporting
confidence: 50%
“…GLUT1 deficiency is seen in 10% of those with typical absence seizures starting before 4 years of age and around 1% of people with typical GGE overall . With a narrow definition of EOAE that excludes not only those with intellectual impairment but also those who have ever had GTCS, myoclonic seizures, or photosensitivity on EEG, the rate of GLUT1 deficiency in EOAE is probably closer to the 1% seen in GGE overall …”
Section: Single Genes and Ggementioning
confidence: 94%
“…Although these subsyndromes are broadly accepted, the diagnostic classification for epilepsy does not draw clear lines between them, and the limits, particularly of CAE, are a matter of active debate. There are also cases that fit the broad definition of GGE but not the classical age at onset, for instance adult‐onset GGE and some early onset absence epilepsies (EOAEs), where seizures start before 4 years of age . There are also situations where the epilepsy is consistent with GGE but intellectual impairment or autism is also present, which fall outside the strict definition of GGE but are important as the genetic causes appear to overlap …”
Section: The Worried Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients inherited the missense mutations from a parent with idiopathic epilepsy including juvenile absence epilepsy and adult-onset absence epilepsy. In a recent study describing the clinical features of children with early-onset absence epilepsy, authors found that SLC2A1 gene mutation is present only in children with atypical clinical features including history of developmental delay, myoclonic or other seizure types and electroencephalography (EEG) findings of 3-4 Hz polyspike discharges [15]. Studies describing familial GLUT-1 DS expanded the spectrum of absence epilepsy [6,8,16].…”
Section: Childhood Absence Epilepsymentioning
confidence: 99%